Stigma, caregiver burden, and expressed emotions: the moderating role of self-compassion in caregivers of substance use disorder - Sageer, Iqra; Asmat, Alia; Sarfaraz, Ayesha; Shahid, Anam (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the moderating effect of self-compassion on the relationship involving stigma, caregiver burden and expressed emotions among caregivers of males diagnosed with substance use disorder. Method: The correlational, quantitative study was conducted from June 1 to September 30, 2021, at the Department of Psychology, University of Central Punjab, Lahore, Pakistan, and comprised caregivers aged 40-55 years living with individuals with substance use disorder and actively performing caregiving duties for at least six months. Data was collected using validated tools. Data was analysed using SPSS 21. Results: Out of the 300 subjects, 54(18%) were males and 246(82%) were females, with overall mean age 45+/-7.73 years. The caregiving duration ranged from 6 months to 20 years. Self-compassion significantly moderated stigma, caregiver burden and expressed emotions (p=0.001). The interaction effects of self-compassion with stigma, affect, behaviour, cognition and caregiver burden collectively explained 88% of the variance in expressed emotion. Self-compassion accounted for a significant change in expressed emotion (p<0.05). Conclusion: Internalised stigma and caregiver burden predicted expressed emotions in caregivers of males with substance use disorder. Key Words: Substance use disorder, Caregiver burden, Self-compassion, expressed emotion.